Pengalaman Kerja, Independensi, Integritas, Kompetensi dan Kualitas Audit di Kantor Inspektorat Provinsi Bali - Anggriawan, Nyoman Diantha; Sukartha, I Made (E-Jurnal Akuntansi; Vol 31 No 12 (2021)DO - 10.24843/EJA.2021.v31.i12.p02, 2021)
This study aims to determine the effect of work experience, independence, integrity, and competence on audit quality at the Bali Provincial Inspectorate Office. The theory used in this research is agency theory. This research was conducted at the Bali Provincial Inspectorate Office. The number of samples taken as many as 32 auditors, with the saturated sampling method. Data was collected through a survey method with data collection techniques using a questionnaire. The analysis technique used is multiple linear regression. Based on the results of the analysis, it was found that work experience, independence, integrity, and competence have a positive effect on audit quality at the Bali Provincial Inspectorate Office. The more work experience an auditor has, the higher the attitude of independence, integrity, and competence possessed, the better the quality of the audit produced. Keywords : Work Experience; Independence; Integrity; Competence; Audit Quality.